Apartheid and the decline of the civilisation idea: an essay on Nadine Gordimer's July's people and J.M. Coetzee's Waiting for the barbarians - Rich, Paul (My University, 1983)
White settler political ideology in South Africa has traditionally seen itself as the embodiment of some form of "civilisation" against the threatened "barbarism" of African majority rule. The term has a significance both in its Victorian imperial roots and its facility for acting as a kind of common ideological denominator binding the political discourse of both Afrikaner and English settlers into a common defence of "white civilisation". Moreover, it reflects the essentially urban nature of white South African society and thus reinforces the apartheid notion of territorial separation between the white urban race in the city areas and the rural abodes of the African majority in the ("precivilised") tribal "Homelands", though limited economic development in certain sections of these rural slums has brought urban aspects even to this originally pastoral vision. The "civilisation" idea, however extends in some respects beyond the simple assertion of white racial ideology in South Africa politics, for it has structured a fair degree of liberal political discourse in the post-war years as well. It was the hope of South African liberals in the churches, the Institute of Race Relations and the Liberal Party itself between 1953 and 1968 that a specifically non-racial "civilisation" could be created in South Africa on the basis of western political and cultural values. This view was influenced both by the perceptions of external views of South Africa politics in the years after 1948 and the equation of the Nationalists' policy of apartheid with many aspects of the Nazi "barbarism" which had been defeated in the second world war. "The rest of the world well understand", wrote the historian Arthur Keppel Jones in a pamphlet What is Destroying Civilisation in South Africa?, "as too few South Africans do, that civilisation is not defined by the colour bar" Unless, however, a shift in policy occurred to admit "non whites" into this "civilisation" then the conclusion emerged that "the verdict of history on the evanescent European civilisation in Southern Africa would be that it was a flame that flickered for only a few generations, and then became a mere historical interlude between two Dark Ages". There was thus an underlying cultural pessimism at the core of the liberal view of protecting the values of a non-racial "civilisation" in the South African context that has deepened in more recent years into one of despair. This cultural Angst has been reflected in two important recent novels by white South African writers that have pinpointed how far liberal or radical white intellectuals in this society have become cut off from the main tenets of western liberal thinking. The burden of this paper is to discuss the cultural and political significance of these two works, Nadine Gordimer's July's People (1981) and J. M. Coetzee's Waiting for the Barbarians (1980) in the context of the historical meaning of the western notion of "civilisation" and the decline of this idea in the era of apartheid ideology in modern South Africa. As the first section of this paper will show, the western "civilisation" idea has been closely linked to an historical and teleological notion of progress allied to imperial expansion since the sixteenth and seventeenth centuries. While in many respects the apartheid conception of racial separation was the fulfillment of many of these precepts, especially in so far as it was allied to the continuation and entrenchment of capitalist economic expansion in Southern Africa, it has been accompanied by a growing loss of faith by liberal intellectuals in the continued progress and extension of western humanistic values. The second section of this paper will thus analyse this clutural Angst among South African liberals before discussing the significance of the two recent works of Gordimer and Coetzee. Novels in the South African context probably have a greater political and ideological significance than most of those written in the metropolitan societies of Western Europe and North America, for the distinction between artistic imagination and political activity is so much thinner.4 To the degree, therefore, that many modern novels can be seen as an extension of more common political and ideological discourse, even if it be that of some form of liberal intellectual salon culture, then they throw some light on the ideological climate of the society concerned. The main test of this, though, must be historical and the centreal thrust of this paper will be to see modern novel writing in South Africa in terms of a set of ideas about both progress and "civilisation" that have become sharply undermined in South Africa's mounting political and ideological crisis of legitimacy.
African Studies Seminar series. Paper presented June 1983
Keywords: Coetzee, J. M.; Waiting for the barbarians; Gordimer, Nadine; July's people; South Africa. Race relations